STUDI EKSPERIMENTAL KEAUSAN SABUK-V STANDAR DAN NON-STANDAR PADA SISTEM TRANSMISI CVT SEPEDA MOTOR MATIC - Semuel M Taribuka; Kristofol Waas; Victor D Waas (Jurusan Teknik Mesin, 2025)
Automatic motorcycles are a type of motorcycle equipped with an automatic transmission system that does not require a manual gear lever for shifting. The gear ratio changes automatically according to the engine speed, allowing the rider to control acceleration solely by adjusting the throttle. The use of an automatic transmission, or Continuous Variable Transmission (CVT), in this system relies on a standard V-belt, as it significantly affects engine performance. However, some motorcycle owners use non-standard belts because they are cheaper, which often leads to faster wear. This study was conducted to determine the wear rate experienced by both standard and non-standard belts after a certain period of use under specific operating conditions. The method used to evaluate belt wear rated an experimental approach, in which the motorcycle was operated at an average speed of 40 km/h over a distance of 24 km for three hours per day, over a period of three months (12 weeks). Each week consisted of 5 days of testing, with the first 6 weeks allocated for the standard belt and the following 6 weeks for the non-standard belt. After the testing period, the belts were removed and their wear was measured. The measurements were compared to the initial data to determine the amount of wear that had occurred. The results showed that the standard belt, after 6 weeks of use (90 hours), experienced wear of: 0.10 mm in diameter, 0.72 mm in upper width, and 0.25 mm in lower width. Meanwhile, the non-standard belt exhibited wear of 0.31 mm in diameter, 0.92 mm in upper width, and 0.78 mm in lower width. Based on these findings, using a standard belt is preferable, as it does not wear as quickly as a non-standard belt. Keywords: automatic motorcycle, V-belt, wear rated.